Peningkatan Nilai Tambah Jagung dari Lahan Suboptimal dengan Mengolah menjadi Nasi Jagung Instan dengan Aplikasi Rehidrasi dan Penambahan Air pada Tepung Jagung - Sugito Sugito; Merynda Indriyani Syafutri; Friska Syaiful; Risbin W. Hutabarat (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2015)
Corn plant is suitable to cultivate on suboptimal land due to it’s resistance to acid and dry soil. The objective of the research was to determine the effect of time soaking corn kernels and addition of water to corn flour on characteristics of instant corn rice. Corn that is used is from the farmers of Arisanjaya village (the area of suboptimal land agriculture). The research used a Factorial Completely Randomized Design with two treatment factors and three replications. The observed treatment factor was soaking time (A1: 6 hours, A2: 12 hours, A3: 24 hours) and the addition of water (B1: 80%, B2: 90%, B3: 100%). Observed parameters were physical (color, texture and length of serving), chemical (moisture, ash) and sensory characteristics with hedonic test (texture, color and flavor). The results showed that the soaking time had significant effect on lightness, chroma and ash content of instant corn rice. The addition water had significant effect on the chroma of instant corn rice. The interaction between the soaking time and addition of water had significant effect on the chroma of instant corn rice. The treatment A1B3 (6 hour soaking time and the addition of water 100%) was the best treatment with the average color values (49.77% lightness, 21.40% chroma, 65.200 hue), 76.73 gf cooked corn rice texture, 9.67 minute length of serving, 4.36% moisture content, 1,01 % ash content, the average value of hedonic test (2.20 texture, 2.56 color, and 1.88 flavor).